Hydrogen Bonding and Relaxation Phenomena in Aqueous Adenine: Ultrasonic and Acoustic Investigations (International Journal of Scientific Research in Science and Technology, 2024)
The molecular interactions of adenine in aqueous solutions were investigated through ultrasonic velocity, density and viscosity measurements at varying molar concentrations and temperatures. From these fundamental properties, a range of thermo-acoustical parameters such as adiabatic compressibility, acoustic impedance, relaxation time, free length, internal pressure and free volume were evaluated. The results reveal strong molecular associations between adenine and water, primarily governed by hydrogen bonding and dipole-induced dipole interactions. Non-linear variations in ultrasonic absorption and compressibility at specific concentrations indicate structural relaxation and molecular aggregation phenomena. This study highlights the utility of ultrasonic and acoustic measurements in elucidating solute-solvent interactions and the structural stability of nucleobase systems.